Kategoria milczenia w staropolskich intermediach szkolnych - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article’s primary focus is the use of silence in Old-Polish allegorical and dramatic interludes. The thesis that the article puts forward is that silence was one of the most important means of scenic expression.